The Impact of Experiments on Students - Steele, Joshua (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2023)
Experiments engage students and improve their academic performance. Studies support this claim through the use of qualitative and quantitative methods. Research also suggests that there is an emotional component to the benefits of experiments. Qualitative results showed an increase in student interest and engagement for students that participated in the experiment. Quantitative results showed an increase in academic achievement for students that participated in the experiment. Scientific discourse also showed to be a valuable component of experiments as the scientific discourse creates a stronger scientific discipline. New programs and research are also generating new ways to analyze the scientific discourse, turning qualitative data to quantitative data. Overall, experiments are useful tools to generate interest and increase academic success.